2019
DOI: 10.1038/s41419-019-2177-x
|View full text |Cite|
|
Sign up to set email alerts
|

Vitamin D promotes the cisplatin sensitivity of oral squamous cell carcinoma by inhibiting LCN2-modulated NF-κB pathway activation through RPS3

Abstract: Chemoresistance is a major cause of cancer progression and the mortality of cancer patients. Developing a safe strategy for enhancing chemosensitivity is a challenge for biomedical science. Recent studies have suggested that vitamin D supplementation may decrease the risk of many cancers. However, the role of vitamin D in chemotherapy remains unknown. We found that vitamin D sensitised oral cancer cells to cisplatin and partially reversed cisplatin resistance. Using RNA-seq, we discovered that lipocalin 2 (LCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 43 publications
2
74
0
1
Order By: Relevance
“…In addition, both up-regulation and intrinsic dysfunctions in ribosomes result in an increased incidence of tumors, and RPS3 is involved in radioresistance or invasion of tumor cells [32,33]. Huang et al showed that Vitamin D promotes the cisplatin sensitivity of oral squamous cell carcinoma by inhibiting LCN2modulated NF-κB pathway activation through RPS3 [34]. Zhao et al unveiled a novel extra-ribosomal role of RPS3 in facilitating hepatocarcinogenesis via the post-transcriptional regulation of SIRT1 expression and proposes that the RPS3/SIRT1 pathway serves as a potential therapeutic target in HCC [35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both up-regulation and intrinsic dysfunctions in ribosomes result in an increased incidence of tumors, and RPS3 is involved in radioresistance or invasion of tumor cells [32,33]. Huang et al showed that Vitamin D promotes the cisplatin sensitivity of oral squamous cell carcinoma by inhibiting LCN2modulated NF-κB pathway activation through RPS3 [34]. Zhao et al unveiled a novel extra-ribosomal role of RPS3 in facilitating hepatocarcinogenesis via the post-transcriptional regulation of SIRT1 expression and proposes that the RPS3/SIRT1 pathway serves as a potential therapeutic target in HCC [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer pharmacological resistance represents the major cause of tumor progression therefore, overcoming drug resistance is now the greatest challenge for scientists. Vitamin D has been reported to reverse resistance mechanisms to chemotherapy [23,24], TKI [28] and other target therapy [25][26][27], as studied in in vitro models of different cancers.…”
Section: Vitamin D and Cancer: Reversal Effects Of Vitamin D On Cancementioning
confidence: 99%
“…Chronic treatment with cisplatin enhanced the protein expression of the oncogene LCN2 by inhibiting methylation at the promoter level. Furthermore, considering that LCN2 overexpression is associated with lymph node metastasis, poor prognosis and post-chemotherapy recurrence, oral cancer cell lines overexpressing LCN2 proteins showed less sensitivity to cisplatin [23]. Surprisingly, vitamin D exposure made oral cancer cells again sensitive to cisplatin by inhibiting LCN2 expression and Nf-kB phosphorylation [23].…”
Section: Vitamin D and Cancer: Reversal Effects Of Vitamin D On Cancementioning
confidence: 99%
See 2 more Smart Citations